Pengembangan Alat Evaluasi Menggunakan Aplikasi Quizizz pada Mata Pelajaran Alquran Hadis di Kelas VII SMP Muhammadiyah Sokaraja - Nur Eka Febriani; Darodjat Darodjat (Proceedings Series on Social Sciences & Humanities, 2023)
In the digital era, evaluation activities are required to use information and Communication Technology (ICT) based evaluation tools such as the Quizizz application. Quizizz app has many features as well as an attractive appearance. The purpose of this study is to find out the development of the Quizizz application in schools, find out the expert assessment of the use of the Quizizz application, find out the practicality and quality of the question items (validity, reliability, differentiability, and difficulty of the question items) used in the research. The type of research used is Research and Development (R&D). The data collection techniques used are observation, interviews, questionnaires, and documentation, while the data obtained are in the form of qualitative and quantitative data. This research was conducted with 8 stages of research and development. Based on the results of the research, the evaluation tool using the Quizizz application is suitable for use as an evaluation tool with a media expert assessment of 86.7% with the criteria of "very valid", an expert assessment of material of 74.3% with the criteria of "valid" and an assessment from the teacher of the Quran hadith lesson class VII 94.7% with the criterion of "very valid". As for the practicality level of 95% with "very practical criteria". The results of the validity test of the questions in the product trial were 4 invalid questions, while in the field trial two questions were invalid. In the reliable test, the question item is declared reliable. In the differentiating power test, the questions in the product trial were 4 questions categorized as bad, 5 questions were categorized as sufficient, 1 question was categorized as good. In the field test, there were 3 bad category questions, 4 sufficient category questions, and 3 good category questions. Based on the difficulty test, the results were obtained in the product trial, 6 easy category questions and 4 medium category questions, while in the field trial 2 easy category questions and 8 medium category questions.